2018
DOI: 10.1002/prep.201700132
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stoichiometry on the Thrust and Heat Deposition of On‐Chip Nanothermites

Abstract: Currently, there is very little systematic work quantifying the thrust or heat applied to an electronic circuit or other substrate by a deposited layer of energetic material. A better understanding of the interactions between nanoscale energetic materials and electronic systems, as a function of stoichiometry, is needed. For this purpose, formulations of nAl-CuO and nAl-Bi 2 O 3 nanothermites were prepared at different equivalence ratios and selectively deposited onto electronic circuit analogues (silicon wafe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…consider. Previous authors have found evidence that slower flame speeds (expected for larger particles) increase the heating of the substrate [41,46]. Whereas, it has been reported that the heat flux maximizes between the peak burn rate (fuel rich) and flame temp (stoichiometric) compositions [28].…”
Section: Heat Production and Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…consider. Previous authors have found evidence that slower flame speeds (expected for larger particles) increase the heating of the substrate [41,46]. Whereas, it has been reported that the heat flux maximizes between the peak burn rate (fuel rich) and flame temp (stoichiometric) compositions [28].…”
Section: Heat Production and Retentionmentioning
confidence: 99%
“…While hot gases can be important for propagating the reaction, gaseous products are overall detrimental to the heating of the substrate [41,46]. The gaseous reactions above the surface (the flame) liberate their energy remotely from the substrate resulting in little surface heating beyond radiant heating.…”
Section: Heat Production and Retentionmentioning
confidence: 99%
“…Due to its relative simplicity, direct writing is widely used for RMS production [12,13,63,[116][117][118]; however, the hazardous and viscous natures of energetic compositions present serious challenges. Therefore, a pipette, syringe or pump can be used to deposit the slurry based on hexanitrohexaazaisowurtzitane (CL-20) and the mixture of two solutions, i. e., the aqueous binder solution and the organic solution of another binder.…”
Section: Diw (Pen-type Robocasting Nanolithography)mentioning
confidence: 99%
“…Application of liquid media improves safety: the electrostatic discharge sensitivity increases from 10-100 μJ for nanothermites in dry state to above 250 mJ for a water-processed system immediately after deposition [179]. Solvent type is also important as suspensions in polar solvents maintain their stability longer [180], which is advantageous for the mixing of nanoparticles [116]. To improve the uniformity of the ink suspension, dispersants are added, typically nonionic or ionic polymers soluble in a dispersing medium, e. g., Zephrym™ PD 2206 and Solsperse™ 32500 [76].…”
Section: Progress In Additive Manufacturing Of Energetic Materialsmentioning
confidence: 99%
“…Generally, MICs are regarded as excellent fuels, which generally consist of metal-fuel (e.g., Al, Mg) and oxidizers that include metal oxides (e.g., MoO 3 [5], Fe 2 O 3 [6], polyvinylidene fluoride [7], NiO [8], CuO [9], and iodates [10]). Compared to traditional micro-MICs, nano-structured MICs have been gradually verified as a promising candidate for highly reactive energetic materials or composites due to their higher heat-release properties, greater contact area 2 of 11 between fuels and oxidizers, and faster detonation velocity [11][12][13]. Therefore, there is an emerging research area of interest in designing novel nano-structured MICs via facile techniques.…”
Section: Introductionmentioning
confidence: 99%